Detection and cultivation of circulating tumor cells in malignant pleural mesothelioma - Bobek, Vladimir; Kacprzak, Grzegorz; Rzechonek, Adam; Kolostova, Katarina (Anticancer research, 2014)
UNLABELLED: Malignant pleural mesothelioma (MPM) is an aggressive disease with very poor prognosis which tends to affect older patients. Progress in the management of this group of patients has been limited by the rarity of the disease and hence, difficulty in conducting randomized trials. The vast majority of cancer deaths occur due to metastasis of the primary tumor to distant sites via circulating tumor cells (CTCs) in the circulation. CTCs are extremely rare and limits in technology used to capture these cells hamper our complete understanding over the metastatic process. In the present study we present a new method for detection and cultivation of CTCs isolated from peripheral blood of MPM patients. PATIENTS AND METHODS: Patients with diagnosed MPM were enrolled into this study. RESULTS: A size-based separation method for viable CTC enrichment from unclothed peripheral blood has been introduced; MetaCell. The size-based enrichment process was based on filtration of peripheral blood (PB) through porous polycarbonate membrane. The separated CTCs are cultured on the membrane in vitro under standard cancer cell culture conditions and observed by an inverted microscope. CONCLUSION: The reported methodology allows for quick and easy enrichment of CTCs and their cultivation. The cultivated cells can be used for next specification of gene expression and histological/biological specificity of concrete mesothelioma.
Keywords: maligní mezoteliom; lidé; Middle Aged; Mesothelioma; separace buněk; Female; circulating tumor cells; nádory plic; MetaCell; Humans; nádory pleury; cultivation; Pleural Neoplasms; Mesothelioma, Malignant; Cell Separation; lidé středního věku; Neoplastic Cells, Circulating; mužské pohlaví; CTC; nádorové cirkulující buňky; ženské pohlaví; Male; Aged; mezoteliom; Lung Neoplasms; senioři